2017
DOI: 10.3390/ani7070052
|View full text |Cite|
|
Sign up to set email alerts
|

A Cultural Conscience for Conservation

Abstract: Simple SummaryThis opinion piece explores how implementing a species royalty for the use of animal symbolism in affluent cultural economies could revolutionise conservation funding. A revenue revolution of this scale is urgently necessary to confront the sixth mass extinction that the planet is now facing. But such a revolution can only occur if the approach to conservation now evolves quickly across disciplines, continents, cultures and economies. This piece is a call to action for research-, culture-, and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Public-private partnerships can also be a key to supporting such projects, such as the current campaign to construct a wildlife crossing to protect cougars in the Santa Monica mountains in Los Angeles, USA (Popescu 2017). Such schemes in Iran could also potentially benefit from innovative funding models that have recently been gaining interest, such as the species royalty system or World Heritage Species concept (Wrangham et al 2008; Good et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Public-private partnerships can also be a key to supporting such projects, such as the current campaign to construct a wildlife crossing to protect cougars in the Santa Monica mountains in Los Angeles, USA (Popescu 2017). Such schemes in Iran could also potentially benefit from innovative funding models that have recently been gaining interest, such as the species royalty system or World Heritage Species concept (Wrangham et al 2008; Good et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The authors wish to make the following change to their paper [ 1 ]. The percentage numbers reflected the quantity in the original version.…”
mentioning
confidence: 99%
“…Conservation funding shortfalls are pushing scientists and conservation donors into searching for innovative funding mechanisms. Good et al (2017) and Courchamp et al (2018) present an example of the latter. They propose that corporations using the imagery of threatened wildlife in their marketing should contribute towards the conservation of those species.…”
Section: Introductionmentioning
confidence: 99%
“…They propose that corporations using the imagery of threatened wildlife in their marketing should contribute towards the conservation of those species. Good et al (2017) suggested that a wildlife imagery royalty would herald a revolution in conservation funding. This idea is not unlike the one proposed by Jepson et al (2011), who called on the film and media industry to contribute financially to the conservation of the species they film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation